Long‐term outcomes of pexidartinib in tenosynovial giant cell tumors. Issue 6 (16th November 2020) - Gelderblom, Hans; Wagner, Andrew J.; Tap, William D.; Palmerini, Emanuela; Wainberg, Zev A.; Desai, Jayesh; Healey, John H.; van de Sande, Michiel A. J.; Bernthal, Nicholas M.; Staals, Eric L.; Peterfy, Charles G.; Frezza, Anna Maria; et al.
Abstract : Background: The objective of this study was to report on the long‐term effects of pexidartinib on tenosynovial giant cell tumor (TGCT). Methods: This was a pooled analysis encompassing 3 pexidartinib‐treated TGCT cohorts: 1) a phase 1 extension study (NCT01004861; 1000 mg/d; n = 39), 2) ENLIVEN patients randomized to pexidartinib (1000 mg/d for 2 weeks and then 800 mg/d; n = 61), and 3) ENLIVEN crossover patients (NCT02371369; 800 mg/d; n = 30). Eligible patients were 18 years old or older and had a histologically confirmed TGCT that was unresectable and symptomatic. Efficacy endpoints included the best overall response (complete or partial response) and the duration of response (DOR) by the Response Evaluation Criteria in Solid Tumors (RECIST) and the tumor volume score (TVS). The safety assessment included the frequency of treatment‐emergent adverse events (TEAEs) and hepatic laboratory abnormalities (aminotransferase elevations and mixed/cholestatic hepatotoxicity). The data cutoff was May 31, 2019. Results: One hundred thirty patients with TGCT received pexidartinib (median treatment duration, 19 months; range, 1 to 76+ months); 54 (42%) remained on treatment at the end of the analysis (26 months after initial data cut of March 2017). The RECIST overall response rate (ORR) was 60%; the TVS ORR was 65%. The median times to response were 3.4 (RECIST) and 2.8 months (TVS), with 48 of the responding patients (62%) achieving a RECIST partial response by 6 months and with 72 (92%) doing so by 18 months. The median DOR was reached for TVS (46.8 months). Reported TEAEs were mostly low‐grade, with hair color changes being most frequent (75%). Most liver abnormalities (92%) were aminotransferase elevations; 4 patients (3%) experienced mixed/cholestatic hepatotoxicity (all within the first 2 months of treatment), which was reversible in all cases (recovery spanned 1‐7 months). Conclusions: This study demonstrates the prolonged efficacy and tolerability of long‐term pexidartinib treatment for TGCT. Abstract : This analysis further illustrates that systemic therapy targeting the CSF1/CSF1R pathway is an effective therapeutic strategy in patients with tenosynovial giant cell tumor. Because of the limited availability of long‐term prospective data for tenosynovial giant cell tumor, these findings are encouraging and demonstrate the overall long‐term benefit of continued treatment with pexidartinib.